The Cost of the Second Seizure: Rethinking the Treatment Decision. Issue 2 (March 2019) - Faught, Edward
Antiepileptic Drug Treatment After an Unprovoked First Seizure: A Decision Analysis Bao EL, Chao LY, Ni P, et al. Neurology . 2018;91(15):e1429-e1439. doi:10.1212/WNL.0000000000006319 Objective: To compare the expected quality-adjusted life-years (QALYs) in adult patients undergoing immediate versus deferred antiepileptic drug (AED) treatment after a first unprovoked seizure. Methods: We constructed a simulated clinical trial (Markov decision model) to compare immediate versus deferred AED treatment after a first unprovoked seizure in adults. Three base cases were considered, representing patients with varying degrees of seizure recurrence risk and effect of seizures on quality of life (QOL). Cohort simulation was performed to determine which treatment strategy would maximize the patient's expected QALYs. Sensitivity analyses were guided by clinical data to define decision thresholds across plausible measurement ranges, including seizure recurrence rate, effect of seizure recurrence on QOL, and efficacy of AEDs. Results: For patients with a moderate risk of recurrent seizures (52.0% over 10 years after first seizure), immediate AED treatment maximized QALYs compared to deferred treatment. Sensitivity analyses showed that for the preferred choice to change to deferred AED treatment, key clinical measures needed to reach implausible values were 10-year seizure recurrence rate ≤38.0%, QOL reduction with recurrent seizures ≤0.06, and efficacy of AEDs on lowering seizure recurrence rate ≤16.3%. Conclusion: Our model determined that immediate AED treatment is preferable to deferred treatment in adult first-seizure patients over a wide and clinically relevant range of variables. Furthermore, our analysis suggests that the 10-year seizure recurrence rate that justifies AED treatment (38.0%) is substantially lower than the 60% threshold used in the current definition of epilepsy.